2015
DOI: 10.1166/nnl.2015.1928
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of P3HT:3C-SiC Composite Structures for Hybrid Photovoltaics

Abstract: In hybrid solar cells, a nanoscale donor/acceptor junction between an organic and an inorganic semiconductor material is mostly established by mixing the organic semiconductor with inorganic nanocrystals or by infiltration into an inorganic nanostructure scaffold. In this report, we describe the characteristics of submicron-sized cubic silicon carbide and its potential as acceptor material in hybrid photovoltaics. The SiC nanocrystals are derived from a sol-gel based precursor after carbothermal reduction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The pristine F8TBT and P3HT films, as deposited by spray-coating show efficient photo-luminescence (PL) under blue/UV laser excitation; with values in the ranges of 10% and 4-5% respectively, in consistency with the literature [16,24]. The as deposited 1:1 blends show a significantly reduced PL emission (Figure 4), as charge-separation at heterojunction interfaces now competes with radiative recombination (PL quenching); the degree of such quenching is also therefore an indicator of likely photovoltaic cell performance [22].…”
Section: Resultssupporting
confidence: 82%
“…The pristine F8TBT and P3HT films, as deposited by spray-coating show efficient photo-luminescence (PL) under blue/UV laser excitation; with values in the ranges of 10% and 4-5% respectively, in consistency with the literature [16,24]. The as deposited 1:1 blends show a significantly reduced PL emission (Figure 4), as charge-separation at heterojunction interfaces now competes with radiative recombination (PL quenching); the degree of such quenching is also therefore an indicator of likely photovoltaic cell performance [22].…”
Section: Resultssupporting
confidence: 82%
“…In particular from hybrid solar cells, it is a well‐known fact that the surface properties of the inorganic component substantially determine the efficiency of the device, for example, via surface trap states fostering trap‐mediated recombination or inter‐particle charge transport limitations, caused by their stabilizing ligands . In the case of silicon carbide nanoparticles within a conjugated polymer matrix, Kettner et al have observed extended emission lifetimes, assigned to the formation of longer lived polarons upon photoinduced electron transfer to the inorganic acceptor or surface trap states, which have been suggested in either case to be beneficial for their function in hybrid photovoltaics . However, also here the surface is the most crucial point, when incorporating SiC nanoparticles into the organic semiconductor matrix of a hybrid solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…[16,19] This motivates a broadening of SiC's application range towards new fields, such as the electronic acceptor in organic/inorganic hybrid photovoltaics, as robust photoelectrode in catalysis and for nanostructured blue light emitters, where nanoscale or large surface area is required. [20][21] In particular from hybrid solar cells, it is a well-known fact that the surface properties of the inorganic component substantially determine the efficiency of the device, e.g. via surface trap states fostering trap-mediated recombination or inter-particle charge transport limitations, caused by their stabilizing ligands.…”
Section: Introductionmentioning
confidence: 99%